Selecting high performance rootstocks for pistachio cultivars under salinity stress based on their morpho-physiological characteristics. (14th September 2020) - Raoufi, Ahmad; Rahemi, Majid; Salehi, Hassan; Javanshah, Amanollah
ABSTRACT: In Iran, the most pistachio orchards are located in semi-arid regions and irrigated with saline water which influences their growth and yield. The present investigation was conducted to evaluate the effects of salinity on growth, and morpho-physiological parameters of six pistachio genotypes as rootstock (ʽAkbariʼ, ʽAhmad-Aghaiʼ, ʽUCB-1ʼ, ʽItalyayiʼ, ʽGhazviniʼ and ʽBadamiʼ). Treatments were different salinity concentrations using NaCl at 0.5, 12 and 18 dSm-1 on six genotypes of pistachio. According to the results, by increasing salinity, the FW, DW, number of growing leaves, SPAD index of leaves, chlorophyll content and stomatal conductance were reduced, but electrolyte leakage of leaf and root tissues, soluble sugars and antioxidant capacity were increased. ʽUCB-1ʼ, ʽAkbariʼ and ʽAhmad-Aghaiʼ had the highest leaf area compared to other genotypes under salinity conditions. The lowest leaf abscission was belonged to ʽUCB-1ʼ and its difference was significant with other genotypes. The WUE of ʽUCB-1ʼ reduced and it was higher than ʽAkbariʼ. The growth of ʽUCB-1ʼ significantly declined up to 79.6% under salinity stress. Salinity stress had the lowest adverse effect on the growth of ʽAkbariʼ and ʽAhmad-Aghaiʼ genotypes. There was no significant difference among genotypes in regard to RWC under salinity stress. It can be concluded that ʽUCB-1ʼ, ʽAkbariʼ and to some extent ʽAhmad-Aghaiʼ were tolerant to salinity stress and can be recommended to use as rootstock under moderate salinity conditions.